2020
DOI: 10.3344/kjp.2020.33.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pain relief and functional improvement between methylprednisolone and dexamethasone lumbosacral transforaminal epidural steroid injections: a self-controlled study

Abstract: Background: Previous studies have shown varying results between lumbosacral transforaminal epidural steroid injections (TFESIs) performed with particulate versus non-particulate corticosteroids. The purpose of this study was to investigate the difference in pain relief and functional improvement between particulate and nonparticulate lumbosacral TFESIs in patients who had undergone both injections, sequentially. Methods: This was a self-controlled, retrospective study of 20 patients who underwent both a methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…There have been no serious complications attributed to the use of Table 5. Physicochemical properties of corticosteroids [86].…”
Section: Epidural Steroid Injection (Esi)mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been no serious complications attributed to the use of Table 5. Physicochemical properties of corticosteroids [86].…”
Section: Epidural Steroid Injection (Esi)mentioning
confidence: 99%
“…Recent literature documents that there is no significant difference in pain relief at any point between non-particulate and particulate steroids. There are recommendations that non-particulate steroid preparations should be considered as first-line agents when performing ESI [86,87]. However, further studies are necessary to compare corticosteroid preparations.…”
Section: Epidural Steroid Injection (Esi)mentioning
confidence: 99%
“…Conversely, Park et al [ 81 ] reported that the nonparticulate steroid dexamethasone was statistically less effective than the particulate steroid in terms of pain relief. In 2020, Donohue et al [ 82 ] reported that there was no significant difference in pain relief at any point between nonparticulate and particulate steroids and recommended the use of nonparticulate corticosteroids in ESI given the safety concerns associated with particulate corticosteroids. Considering the potential risk of catastrophic complications, nonparticulate steroid preparations should be considered as first-line agents when performing ESI.…”
Section: Miscellaneous Issues For Safe Esimentioning
confidence: 99%
“…Epidural injections such as the interlaminar epidural block and transforaminal epidural injection (TFEI) have been widely used for the treatment of patients with low back pain and lumbosacral radicular pain [ 1 4 ]. As injection agents, corticosteroids and local anesthetics are commonly used to reduce pain and inflammation [ 5 7 ]. Both interlaminar and transforaminal block techniques are effective for lumbar radiating pain and have low complication rates, but the transforaminal technique can be more effective than the interlaminar [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%